Integrating Technology, Innovation in Teaching and Learning, Entrepreneurship Education on Academic Achievement of Office Technology and Management Students in Southwest Colleges of Education, Nigeria - Bintu, Fehintola Fatimoh (Mahesa Research Center, 2025)
This paper explores the integration of technology and innovation in teaching entrepreneurship education to improve Office Technology and Management (OTM) students’ academic achievement in Southwest Nigeria Colleges of Education. While Technology enhances engagement, motivation, and learning outcomes generally, its use in OTM entrepreneurship education remains underexplored. The mixed-methods study examined the impact of innovation on outcomes like mindset, skills, and knowledge. Surveys of 300 students and interviews with 15 educators revealed that technology can boost engagement, motivation, and participation. The key elements, like points, badges, leaderboards, and simulations, were identified for curriculum integration. The study recommends developing innovative technology-based entrepreneurship programmes and provides a framework for educators. It contributes insights for educators, policymakers, entrepreneurs, and students on innovation in education and entrepreneurship.